Last resort - Buzby, Zane; Grodin, Charles; Lovitz, Jon; Rose, Robin Pearson; Mullally, Megan; Trinity Pictures, Inc.; Concord Pictures (Firm); Buena Vista Home Entertainment (Firm) (Burbank, California Buena Vista Home Entertainment, 2006)
Club Sand is a tropical resort in the Caribbean where "deluxe accommodations" are army cots, counselors specialize in seduction and armed guerrillas could invade any minute.
Title from disc label. Credits from IMBd.
Full screen presentation.
DVD release of the 1986 motion picture.
Special features: original trailer, cast biographies.
Executive producer, Nessa Cooper ; music, Steve Nelson and Thom Sharp.
Charles Grodin, Jon Lovitz, Robin Pearson Rose, Megan Mullally.
Keywords: Hotels -- Caribbean Area -- Drama; Vacations -- Caribbean Area -- Drama; Seduction -- Drama; Hotels; Seduction; Vacations; Caribbean Area; Comedy films; Drama; Feature films